PENGARUH ASET PAJAK TANGGUHAN DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA - Tiara Timuriana; Rezwan Rizki Muhamad (Universitas Pakuan, 2015)
The financial statements of the company produced and prepared as a management accountability to investors so that it reflects the company's activities. The liability is not limited to management purposes but also for the benefit of the tax authorities. The big difference in the spur interest and information management to consider how accounting numbers generated can maximize its interests. How that can be done to influence the management accounting numbers can be the earnings management through deferred tax assets and deferred tax expense in the financial statements. This study aims to: (1) Describing the effects of deferred tax assets on earnings management in manufacturing companies in Indonesia Stock Exchange 2010-2014. (2) Describe the effect of deferred tax expense on earnings management in manufacturing companies in Indonesia Stock Exchange 2010-2014. (3) Describe the effect of deferred tax assets and deferred tax expense on earnings management in manufacturing companies in Indonesia Stock Exchange 2010-2014. Data processing method is by descriptive statistical analysis with analysis tools that multiple linear regression. Research shows that: (1) Assets Deferred tax effect on earnings management, (2) Deferred tax expense has no effect on earnings management, and (3) Deferred tax assets and deferred tax expense jointly effect on earnings management.Key words: Asset deferred tax, deferred tax expense, and earnings management